Moving beyond punitivism: Punishment, state failure and democracy at the margins. (April 2017) - Koch, Insa
Recent commentary on the punitive turn has focused on the repressive nature of criminal justice policy. Yet, on a marginalised council estate (social housing project) in England, residents appropriate the state in ways that do not always align with the law. What is more, where the state fails to provide residents with the protection they need, residents mobilise informal violence that is condemned by the state. An ethnographic analysis of personalised uses of criminal justice questions the state-centric assumptions of order that have informed recent narratives of the punitive turn. It also calls for a reassessment of the relationship between democratic politics and criminal justice by drawing attention to popular demands that are not captured by a focus on punishment alone.